Ang Pakigbato kang mga Sibalomnon Religio-political struggles of the Sibalomnon (1838-1946). - Tan, Nikki Coleen O
The study is about the religious and political struggles of the Sibalomnons from 1838 when Agustin de Baladjay became the gobernadorcillo of Sibalom to 1946 when Sibalom was already liberated from the Japanese. The study aimed to provide answers to the following questions: (1) Who led the various struggles in Sibalom against the colonizers and what were their exploits?, (2) What were the grievances and factors that led them to stage these struggles and revolts?, (3) What were the military tactics employed by the Sibalomnon leaders and their followers during the Spanish, American, and Japanese occupations?, and (4) What was the significance of the revolts staged by the Sibalomnons?, The data gathering techniques employed by the researcher were library work, oral interview and photo documentation. Almost all information regarding the Spanish and American periods were taken from books and articles while almost all the information regarding the Japanese period were taken from oral interviews of former guerilla members. The researcher found out that the persons well-known to the Sibalomnons who led the struggles and rebellions were Agustin Rafael "Osting" Baladjay, Gregorio Palmero a.k.a. Dios Gregorio of the Igbaong Rebellion, Quintin Serado, General Leandro Fullon, and Colonel Valentin Gasparil. The grievances which stirred these revolts were religious persectution, patriotism, and the inhuman acts of the Japanese. The military tactics that they employed was a transition from conventional warfare to guerilla fighting. The researcher found out that one of the important results of the struggles on the religious side is the establishment of the Iglesia Filipina Idependiente and for the political side, it is political autonomy.